Continental thunderstorm ground enhancement observed at an exceptionally low altitude - I. Kolmašová; I. Kolmašová; O. Santolík; O. Santolík; J. Šlegl; J. Šlegl; J. Popová; Z. Sokol; P. Zacharov; O. Ploc; G. Diendorfer; R. Langer; et al. (Atmospheric Chemistry and Physics, 2022)
Two long-lasting thunderstorm ground enhancement (TGE) events were registered at the Milešovka meteorological observatory in Czechia (50.55∘ N, 13.93∘ E; 837 m altitude) on 23 April 2018, during linearly organized thunderstorms. Two intervals of increased photon counts were detected by a plastic scintillator, respectively lasting 70 and 25 min and reaching 31 % and 48 % above the background radiation levels. Using numerical simulations, we verified that the observed increases in count rates are consistent with the energy spectrum of previously observed TGEs. We investigated the relevant data from a suite of meteorological instruments, a Ka-band cloud radar, an electric field mill, and a broadband electromagnetic receiver, all placed at the Milešovka observatory, in order to analyse the context in which these unique continental TGEs occurred at an exceptionally low altitude. The onset of the TGEs preceded the onset of precipitation by 10 and 3 min, respectively, for the two events. Both this delayed rain arrival and an energy threshold of 6.5 MeV for registered particles clearly exclude the detection the decay products of the radon progeny washout during the TGE intervals. At the same time, the European lightning detection network EUCLID detected numerous predominantly negative intracloud lightning discharges at distances closer than 5 km from the particle detector, while the occurrence of cloud-to-ground discharges was suppressed. The cloud radar recorded presence of graupel below the melting level, and the composition of hydrometeors suggested good conditions for cloud electrification. The observed variations in the near-surface electric field were unusual, with very brief negative-electric-field excursions reaching −20 kV in a quick succession. At the same time, sub-microsecond unipolar pulses emitted by close corona discharges saturated the broadband magnetic loop antenna. All these measurements indicate that a strong lower positive-charge region was present inside the thundercloud. The bottom thundercloud dipole was probably responsible for acceleration of the seed electrons in the air. These seed electrons might originate in the secondary cosmic ray particles but could also come from a high concentration of radon in the air collected during the propagation of the convective system above the uranium-rich soils before the thunderstorms overpassed the Milešovka observatory.